The Role of International Development Agencies - David, Randolf S. (Kasarinlan: Philippine Journal of Third World Studies; Vol 4 No 2 (1988), 2009)
One of the ironies surrounding international development assistance is that while it purports to help liberate people from those conditions which enslave them, the very act of offering assistance already constitutes a potential constraint to the liberative process. Historically, international aid has been one of the abiding instruments of intervention in the affairs of another country. Yet at the same time, the ethic of global solidarity requires that local efforts at liberation from the disabling conditions of poverty, oppression, and domination must be enhanced and strengthened as if it was the whole global moral community itself that is offended by the persistence of these conditions. Concerned individuals working in international development agencies have a moral obligation to ensure that international assistance does not become the vehicle for new intervention or the seed for new forms of dependence. Political and business groups in the donor countries are known to be adept in exploiting such relationships for their own benefit. Great care should be taken that their influence does not determine the shape of the assistance offered. The best way to protect the integrity of an international assistance program both from domestic and foreign opportunists is for the international donor agency to draw a coherent vision of its work in a country and to transparently premise all its activities and projects on such a vision. The concrete meanings of this vision must be articulated and carefully reviewed and assessed from year to year in the light of the unfolding realities they confront.